1999
DOI: 10.1016/s0304-3959(99)00081-0
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of factors that contribute to the magnitude of placebo analgesia in an experimental paradigm

Abstract: Placebo analgesia was produced by conditioning trials wherein heat induced experimental pain was surreptitiously reduced in order to test psychological factors of expectancy and desire for pain reduction as possible mediators of placebo analgesia. The magnitudes of placebo effects were assessed after these conditioning trials and during trials wherein stimulus intensities were reestablished to original baseline levels. In addition, analyses were made of the influence of these psychological factors on concurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
326
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(349 citation statements)
references
References 16 publications
19
326
0
4
Order By: Relevance
“…Previous work has shown that the prospect of reduced pain can reduce the pain reported in response to a noxious stimulus. [84][85][86][87][88] The "inclusion/ exclusion" session provided an expectation that head pain would increase during the interventions and cease immediately after cessation of the technique. However, participants had no prior expectation of the likely course of referred head pain as the technique was sustained.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the prospect of reduced pain can reduce the pain reported in response to a noxious stimulus. [84][85][86][87][88] The "inclusion/ exclusion" session provided an expectation that head pain would increase during the interventions and cease immediately after cessation of the technique. However, participants had no prior expectation of the likely course of referred head pain as the technique was sustained.…”
Section: Discussionmentioning
confidence: 99%
“…As can be expected, the pain ratings in both groups were identical from day 1 until day 5, and only then diverged significantly on days 6 to 8: The control group habituated and the context group did not. The placebo effect may occur through both expectation and conditioning mechanisms (Colloca and Benedetti, 2005), and a correlation between the degree of expected treatment effect and the subsequent placebo-induced analgesia has been observed (Price et al, 1999). Importantly, we did not use learning or conditioning paradigms, i.e., the negative information was only once given verbally.…”
Section: Discussionmentioning
confidence: 99%
“…After 15 min waiting time (allegedly for the medication to take effect), the placebo analgesic effect was amplified by a classic conditioning procedure commonly used and proven to be effective in placebo analgesia studies (51). More specifically, participants were exposed to a series of four stimuli delivered with an intensity of stimuli rated between "3" and "4" during the calibration procedure.…”
Section: Methodsmentioning
confidence: 99%